2018
DOI: 10.3390/medicines5030081
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of the Pharmaceutical Potential of Juniperus L. Metabolites

Abstract: Background: Plants and their derived natural compounds possess various biological and therapeutic properties, which turns them into an increasing topic of interest and research. Juniperus genus is diverse in species, with several traditional medicines reported, and rich in natural compounds with potential for development of new drugs. Methods: The research for this review were based in the Scopus and Web of Science databases using terms combining Juniperus, secondary metabolites names, and biological activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 124 publications
1
24
0
Order By: Relevance
“…badia protein extracts, and to a far greater extent ( p < 0.05) of Joba extract. Recent studies showed that phenolic compounds from Juniperus could induce apoptosis in HT29 cells [22,23]. In this work, no cytotoxic effects were detected with protein extracts, but the significant reduction in cancer cell invasion and the results obtained in Figure 3 suggest that these results could be related to MMP-9 inhibition abilities observed in Joba.…”
Section: Discussionsupporting
confidence: 47%
“…badia protein extracts, and to a far greater extent ( p < 0.05) of Joba extract. Recent studies showed that phenolic compounds from Juniperus could induce apoptosis in HT29 cells [22,23]. In this work, no cytotoxic effects were detected with protein extracts, but the significant reduction in cancer cell invasion and the results obtained in Figure 3 suggest that these results could be related to MMP-9 inhibition abilities observed in Joba.…”
Section: Discussionsupporting
confidence: 47%
“…Some alkaloids, flavonoids, glycosides, tannins, phenolic compounds, and steroids from JCo berries and leaves can be extracted using chloroform and methanol [23]. The pharmacological activities of these chemical constituents include anti-inflammatory [24,25], antifungal [26], analgesic [27], hepatoprotective [23], antimicrobial, anti-mycobacterial [28,29], and neuroprotective [22] effects. In a recent study, Benzina et al demonstrated that deoxypodophyllotoxin extracted from JCo induced apoptosis in breast cancer cells [30].…”
Section: Introductionmentioning
confidence: 99%
“…Application of J. communis is used in the treatment of urinary tract problems, migraine headaches, diabetes, gonorrhea, and skin irascibility. Reports of other studies have elucidated the feasibility of Juniperus species to be used as anti‐atopic, anticancer (lung, liver, bladder, and breast carcinomas), anxiolytic, antifungal, antimicrobial, pharmaceutical preservatives, and spices (Tavares & Seca, 2018).…”
Section: Traditional and Ethnopharmacological Properties Of Thymoquinonementioning
confidence: 99%